2016
DOI: 10.1002/marc.201500661
|View full text |Cite
|
Sign up to set email alerts
|

Influence of RNA Strand Rigidity on Polyion Complex Formation with Block Catiomers

Abstract: Polyion complexes (b-PICs) are prepared by mixing single- or double-stranded oligo RNA (aniomer) with poly(ethylene glycol)-b-poly(L-lysine) (PEG-PLL) (block catiomer) to clarify the effect of aniomer chain rigidity on association behaviors at varying concentrations. Here, a 21-mer single-stranded RNA (ssRNA) (persistence length: 1.0 nm) and a 21-mer double-stranded RNA (small interfering RNA, siRNA) (persistence length: 62 nm) are compared. Both oligo RNAs form a minimal charge-neutralized ionomer pair with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
105
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 70 publications
(113 citation statements)
references
References 30 publications
8
105
0
Order By: Relevance
“…Above a critical association concentration (CAC), uPICs undergo secondary assembly into micellar PICs (mPICs). This two-step self-assembly is clearly demonstrated when single-strand RNA (ssRNA) (21-mer) is combined with PEG-poly(Llysine) (PEG-PLys) (MW of PEG (MW PEG ): 12,000, degree of polymerization of PLys (DP PLys ): ~40) ( Figure 4B) (20). At lower concentrations (< 0.01 mg/mL), the formation of small PICs with a hydrodynamic diameter (D H ) of ~10 nm is clearly observed, corresponding to the primary assembly step, i.e., uPICs.…”
Section: Basics Of Block Copolymer Self-assemblymentioning
confidence: 99%
See 1 more Smart Citation
“…Above a critical association concentration (CAC), uPICs undergo secondary assembly into micellar PICs (mPICs). This two-step self-assembly is clearly demonstrated when single-strand RNA (ssRNA) (21-mer) is combined with PEG-poly(Llysine) (PEG-PLys) (MW of PEG (MW PEG ): 12,000, degree of polymerization of PLys (DP PLys ): ~40) ( Figure 4B) (20). At lower concentrations (< 0.01 mg/mL), the formation of small PICs with a hydrodynamic diameter (D H ) of ~10 nm is clearly observed, corresponding to the primary assembly step, i.e., uPICs.…”
Section: Basics Of Block Copolymer Self-assemblymentioning
confidence: 99%
“…The D H of oligonucleotideloaded mPICs prepared from PEG-PLys is reported to range from 40 to 80 nm with a narrow size-distribution (polydispersity index in dynamic light scattering, µ2/ Γ 2 < 0.1) (21,22). The smaller mPICs were constructed using PEG-PLys with shorter PLys segments, e.g., DP PLys = ~20 and ~40, whereas PEG-PLys with a longer PLys segment (DP PLys = ~80) generated the larger mPICs (20,22). Thus, the smaller mPICs are potentially highly efficient for permeation within solid tumor tissues, in contrast with lipid nanoparticles with a D H of ~90 nm (23).…”
Section: Design Of Block Copolymers For Nucleic Acid Deliverymentioning
confidence: 99%
“…35 Either 21-mer single-strand RNA or double-strand RNA (dsRNA) was mixed in an aqueous solution with PEG-PLys. The DP of the PLys segment was fixed at 40, and the molecular weight of the PEG segment was systematically varied in the range from 2k to 42k.…”
Section: Unit Pics and Micellesmentioning
confidence: 99%
“…Thus, no significant increase in the positioning freedom in the PIC phase is expected to compensate for the increased steric repulsion of the PEG strands in the PIC micelle structure, and dsRNA/PEG-PLys remains as uPICs in aqueous media. 35 The formation of a stable uPIC structure from dsRNA is used to construct a palisade of block ionomers to pair with dsRNA (small interfering RNA) onto gold nanoparticles to create systemically injectable nanocarriers to deliver small interfering RNA therapeutics to target organs to treat cancer. 36,37 …”
Section: Unit Pics and Micellesmentioning
confidence: 99%
“…[102] Interestingly, in a subsequent investigation, RNA strand rigidity was found to influence the formation of a unimer versus a PEC micelle. [103] Hayahsi et al found that double stranded RNA formed unimer PEC complexes, whereas single stranded RNA was able to form a PEC micelle. [103]…”
Section: Polypeptide Micellar Polyelectrolyte Complexesmentioning
confidence: 99%